2015
DOI: 10.1039/c5ta01842k
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle prepared mechanically stable hierarchically porous silica granulates and their application as oxygen carrier supports for chemical looping combustion

Abstract: Viamodifying the templating synthesis of hierarchical nanomaterials, a strategy was proposed to generate bi-modal porous granulates with mechanical stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…To date, however, particle size as a key operational variable for the application of α-Fe 2 O 3 as an oxygen carrier has not been closely examined, especially for nanoparticles with a primary particle size below 100 nm in diameter. Recent investigations have revealed that using nanoparticles instead of more conventional, larger millimeter- or micrometer-sized particles may hold several advantages for performance, including increasing reactivity, decreasing mass resistance, and promoting heat transfer, which facilitates oxygen carrier performance at lower temperatures. Most previous studies have focused on α-Fe 2 O 3 particle sizes ranging from micrometers to millimeters and have found that decreasing particle size leads to an increase in the rate of α-Fe 2 O 3 reduction and a decrease in the temperature required for the reduction reaction to proceed. , For example, Pang and co-workers found that a decrease in α-Fe 2 O 3 particle size from ∼100 to 2 μm led to a reduction in the activation energy necessary for α-Fe 2 O 3 reduction by H 2 from 78.3 to 36.9 kJ/mol across a temperature range from 450 to 600 °C. These results illustrate the promise of tailoring α-Fe 2 O 3 particle size to further improve process efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, particle size as a key operational variable for the application of α-Fe 2 O 3 as an oxygen carrier has not been closely examined, especially for nanoparticles with a primary particle size below 100 nm in diameter. Recent investigations have revealed that using nanoparticles instead of more conventional, larger millimeter- or micrometer-sized particles may hold several advantages for performance, including increasing reactivity, decreasing mass resistance, and promoting heat transfer, which facilitates oxygen carrier performance at lower temperatures. Most previous studies have focused on α-Fe 2 O 3 particle sizes ranging from micrometers to millimeters and have found that decreasing particle size leads to an increase in the rate of α-Fe 2 O 3 reduction and a decrease in the temperature required for the reduction reaction to proceed. , For example, Pang and co-workers found that a decrease in α-Fe 2 O 3 particle size from ∼100 to 2 μm led to a reduction in the activation energy necessary for α-Fe 2 O 3 reduction by H 2 from 78.3 to 36.9 kJ/mol across a temperature range from 450 to 600 °C. These results illustrate the promise of tailoring α-Fe 2 O 3 particle size to further improve process efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Using copper oxide nanoparticle Liu et al (2015) reported greater ability to resist fatigue stress and high porosity greater than 0.7 cm 3 /g with noticeable pore on the outer surface. Copper oxide was formed by dry impregnated against methanol solution with silica as support material.…”
Section: Nanoparticle-based Oxygen Carriermentioning
confidence: 98%
“…In recent years, metal oxide based nanomaterials are emerging in various areas such as thermal barrier [1], gas sensor [2], solar cells [3], drug delivery [4], and biomedical applications [5] due to ease of preparation and possibility in tailoring chemical and physical properties. Nanoporous oxide materials possess tremendous applications in water purification [6], biosensors [7], therapeutics [8], optical sensors [9], oxygen carrier [10], battery technology [11], and bioimaging [12]. Overall, nanoporous anodized alumina (NAA) has several advantages such as high surface area to volume ratio, thermal stability, chemical stability, electrical insulation, formation of unique pore structures, high porosity, self-organized pore structure, being nontoxic and bioactive, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%